A rare case of omental torsion - a surprise diagnosis of acute pelvic pain - Raza, Naimah; Kania, Prema; Bhamare, Prashant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Omental torsion is a rare cause of acute abdominal or pelvic pain. It is rarely diagnosed pre-operatively. It poses a great challenge as it closely mimics the other conditions causing acute surgical abdomen, such as appendicitis, ovarian torsion, ruptured ovarian cyst or ectopic pregnancy etc. Hence, often it presents as a surprise intra-operative diagnosis. Though exploratory laparotomy represents the diagnostic and definitive therapeutic procedure, presently Laparoscopy is the first choice procedure.